The effects of multimodal cocktail analgesic local injection in postoperative pain control after laminoplasty: A study protocol of a prospective randomized controlled trial - Jaewan Soh; Hong-Sik Park; Won-Young Lee; Se-Hwan Park; Kyung-Chung Kang (PLoS ONE, 2025)
Background Laminoplasty is the most widely used surgical technique for cervical spondylotic myelopathy. This surgery can cause severe postoperative pain; if not controlled, recovery or rehabilitation may be delayed. Therefore, effective control of postoperative pain is crucial. This randomized prospective study aims to evaluate the effects of a multimodal cocktail injection on postoperative pain and the efficacy of the protocol in patients undergoing posterior laminoplasty for cervical myelopathy. Methods This single-center prospective randomized controlled trial focuses on patients diagnosed with cervical myelopathy or radiculopathy. This study will include patients aged 20–80 years who underwent laminoplasty. Participants will be divided into two groups: one group will receive a multimodal cocktail local injection during surgery and the other group will receive a local injection of normal saline only. The study is scheduled for a 3 month follow-up. The primary outcome measure will be the visual analog scale (VAS) score. Secondary outcome measures will be opioid and rescue analgesic consumption, time of initial analgesic requirement, adverse effects, and Japanese Orthopaedic Association (JOA) and neck disability index (NDI) scores. Results and conclusions This is the first prospective randomized controlled trial to analyze the effects and safety of multimodal cocktail injections after cervical laminoplasty. Through this study, we anticipate that the demonstration of potential usefulness of multimodal cocktail analgesic injections in various aspects of spinal surgery, thereby this will provide a protocol for intraoperative cocktail injection. Trial registration This trial was registered at the (https://www.clinicaltrial.gov), (NCT06113497) on 11/12/2023.